Deterministic preparation of a tunable few-fermion system - Serwane, Friedhelm; Zürn, Gerhard; Lompe, Thomas; Ottenstein, Timo Bastian; Wenz, André Niklas; Jochim, Selim (Science, 2011)
Systems consisting of few interacting fermions are the building blocks of matter, with atoms and nuclei being the most prominent examples. We have created a few-body quantum system with complete control over its quantum state using ultracold fermionic atoms in an optical dipole trap. Ground-state systems consisting of 1 to 10 particles are prepared with fidelities of ∼90%. We can tune the interparticle interactions to arbitrary values using a Feshbach resonance and have observed the interaction-induced energy shift for a pair of repulsively interacting atoms. This work is expected to enable quantum simulation of strongly correlated few-body systems.